The reality and prospects of desert tourism in Algeria The state of Biskra is a case study - Bechara, Samir (Journal of Architecture and environment of child, 2021)
Saharan tourism theme is considered one of the most important topics of interest to the Algerian state in recent years and as an alternative and strategic choice of sustainable development alternatives in developing and diversifying the national economy, this is because it provides all the elements for success if there is a strategic tourism planning based on Correct foundations. We chose the Biskra state as a case study in our research in order to diagnose and evaluate the reality of the tourism sector in it, By shedding light on the hotel barn, tourism promotion, and tourism demand. The study showed that the state has many qualifications and components, which makes it a pioneer in the tourism sector, However, this sector did not live up to the required level according to the results obtained. This made us put together a set of recommendations that would develop tourism in the wilaya of Biskra in particular and Algeria in general. This made us put a set of recommendations that would develop tourism in the Biskra state in particular and Algeria in general.